Investigation of the Occurrence of Progressive Collapse in High-Rise Steel Buildings with Different Braced Configurations - Saberi, Hamid; Saberi, Vahid; Sadeghi, Abbasali; Pooyasefat, Abbas; Noroozinejad Farsangi, Ehsan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The progressive collapse phenomenon refers to a chain of damages in a structure where all or a large part of the structure is destroyed by an initial local collapse in it, which can lead to very disastrous results. Therefore, the prevention of progressive collapse has become a necessary action in the design and analysis of buildings and it is vital to investigate this topic more accurately.
Keywords: high-rise steel buildings; progressive collapse; nonlinear dynamic analysis; Alternative Path Method (APM); concentric bracing; GSA guideline; wysokie budynki stalowe; postępujące zawalenie; łańcuch uszkodzeń konstrukcji; metoda APM